Enchaning Chemistry Learning with a Local Wisdom-Based E-Encyclopedia for High School Students - Zulyanti; Raudhatul Fadhilah; Rismahardian A. Kurniawan (Postgraduate, University of Mataram, 2025)
This study explores the integration of local cultural knowledge into high school chemistry education through the development of an E-Encyclopedia. Aimed at improving student comprehension of chemical elements, this educational resource contextualizes complex scientific concepts with culturally relevant examples. The E-Encyclopedia was created following the ADDIE model and validated through expert reviews and user feedback. The results showed high validation scores and positive reception from both teachers and students, with usability ratings of 88.09% from educators and 85.93% from learners. These findings suggest that the E-Encyclopedia is an effective tool for making chemistry education more engaging and accessible.